Invasive Lobular Carcinoma of the Male Breast: A Rare Histology in an Uncommon Disease - Briest, Susanne (S. Karger GmbH, 2009)
SUMMARY: BACKGROUND: Breast cancer in men is an uncommon disease. Nearly all cases of male breast cancer originate in the terminal ductulolobular unit, with exceedingly rare reports of lobular carcinoma in men. Invasive lobular cancer is found in no more than 1-2% of male breast cancer cases. Most of what is known about this disease is in the form of approximately 30 case reports in the literature. CASE REPORT: We report the case of a 52-year-old man who presented at our institution with a lump in his left breast. Ultrasound-guided biopsy revealed an invasive lobular cancer. The rare histological type was confirmed by the result of the histological examination of the mastectomy specimen. The treatment was completed by dose dense chemotherapy, radiation, and endocrine therapy. CONCLUSION: Even though lobular structures are quite infrequent in the normal male, sporadic cases of invasive lobular breast cancer have been described. A short overview will be given in this case report.